2018
DOI: 10.1038/s41426-017-0008-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of tuberculosis in the head and neck region—11 years’ experience and a review of the literature

Abstract: Tuberculosis (TB) is an infectious disease and major health concern. Head and neck tuberculosis (HNTB) is relatively rare, but can arise in many regions, including the lymph nodes, larynx, oral cavity and pharynx. We retrospectively reviewed the clinical records of 60 patients diagnosed with HNTB in our department between March 2005 and January 2016. A review and summary of previous HNTB articles published in PubMed since 1885 was also performed. The subjects consisted of 17 males and 43 females, and the avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 29 publications
3
34
1
9
Order By: Relevance
“…The N7 subtype phylogeny shows that sequences of those IAVs isolated in Argentina, all from silver teals, are unique and share no relationship with those obtained from wild bird isolates in Chile 20 or Peru 19 (SFig. 18 , red branches).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N7 subtype phylogeny shows that sequences of those IAVs isolated in Argentina, all from silver teals, are unique and share no relationship with those obtained from wild bird isolates in Chile 20 or Peru 19 (SFig. 18 , red branches).…”
Section: Resultsmentioning
confidence: 99%
“…The phylogenetic analysis of the internal gene segments from the Argentinean IAVs showed shared ancestry with equine-origin IAVs (PA, NP, NS-A), and avian-origin IAVs of Eurasia (PB2), North America (PB1, M, NS-B) and Antarctica (PA, M), demonstrating that their genetic diversity has been shaped by multiple introductions and reassortment occurring as early as the end of the 19th century 15 . Interestingly, the IAVs isolated from wild birds in Argentina have all internal gene segments of SAm origin, while many Chilean and Peruvian viruses have either all or most of their internal genes segments of NAm origin, and close to those from Central America 19 , 20 , 46 . More recently, H5N5 isolates from Antarctica were shown to carry gene constellations of NAm origin 7 , 18 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound images in the present study showed that edge-blurring, mixed echo or hyperechoic and calcified lesions are consistent with a diagnosis of lymph node tuberculosis. The necrotic lymph nodes are characterized by relatively sharp edges, low echo and no calcification [18]. Therefore, ultrasound imaging is helpful for a differential diagnosis of the two diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 10% of cases of extrapulmonary TB are found in the head and neck region and 10% of those cases present in the oral cavity. 1,2 Early differentiation together with prompt multidisciplinary management prevents spread of this deadly disease.…”
Section: Oral Tuberculosismentioning
confidence: 99%